Drug-induced Vasculitis in a Breast Cancer Patient Receiving Chemotherapy - Nasrolahi, Hamid; Omidvari, Shapour; Javid, Seyed Ahmad; Hamedi, Seyed Hasan; Mohammadianpanah, Mohammad; Ansari, Mansour; Ahmadloo, Niloofar; Mosalaei, Ahmad (Reports of Radiotherapy and Oncology, 2024)
Introduction: Drug-induced vasculitis following chemotherapy has been rarely reported. We report such a case of drug-induced vasculitis following chemotherapy in a breast cancer patient. Report of the case: A 52 year old woman with stage III breast cancer developed pathologically proven vasculitis presenting as bilateral severe erythema, edema and ulceration on both feet 10 days following the 4th cycle of adjuvant chemotherapy. Chemotherapy consisted of docetaxel, doxorubicin, and cyclophosphamide in each cycle that was preceded by premedication including dexamethasone, granisetron, and H1 and H2 blockers. Furthermore, filgrastim (5µg/kg) was administered following each cycle of chemotherapy during days 5-9. By discontinuing chemotherapy and starting high-dose intravenous methylprednisolone, vasculitis was resolved. The patient did not experience vasculitis following the re-challenge of chemotherapy excluding docetaxel and filgrastim. Conclusion: This case suggests that docetaxel and filgrastim might be added to the list of agents causing drug-induced vasculitis.